PENGARUH LINGKUNGAN KERJA, KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. RAJA BESI SEMARANG - Hendra Hermawan, 10.05.51.0013; Wanuri, Wanuri (Students Journal of Economic and Management, 2014)
The study analyzed the influence ofÂ work environment, competence and compensation to performance. The research object in this paper is the in PT. Raja Besi Semarang 100 sample. Sampling technique in this study is simple random sampling is random sampling by using the method of data collection questionnaire (questionnaire) by distributing a list of statement to the respondents in order to obtain information. The purpose of the study was formulated to look for answers that affect employee performance. The data were analyzed using the data to the normality test variable regression model gadfly or residuals have a normal distribution, the classical assumption of multicolinearity test to test correlation between the independent variables, factor analysis to test the validity of the question items, cronbach alpha to test the reliability of the instrument, regression analysis, to examine the influence of the partial of each independent variable was tested with the coefficient of determination (R2), F test and t test model to test and prove partial effect of each independent variable. The results of the research are : (1) Work Environment has a positive and significant impact on employee performance in PT. Raja Besi Semarang. (2) Competence has a positive and significant impact on employee performance in PT. Raja Besi Semarang. (3) Compensation has a positive and significant impact on employee performance in PT. Raja Besi Semarang. Keywords: Work Environment, Competence, Compensation, Employees Performance